Parameter Extraction Method of Meta Equivalent Circuit Based on VIE-MoM-PEEC Algorithm - Wu, Xin; Liu, Haiyan (Distributed Generation & Alternative Energy Journal, 2025)
Equivalent circuit parameter extraction can reflect the electrical characteristics of actual components or systems, but there are problems such as parameter correlation at different scales, balance between calculation accuracy and efficiency in the process of circuit extraction. A new method for extracting circuit parameters is proposed. This method combines the volume integral equation algorithm and the method of moments to handle both dielectric and conductor regions. Classical surface-based and edge-based basis functions are used to discretize the conductor structure, ensuring numerical stability and convergence. In addition, multi-branch basis functions are introduced for port excitation modeling, which improves the simulation accuracy for complex port geometries. The experimental results show that the voltage pressure test results and time differences are 0.01, 0.02, 0.02, 0.03 in 697 to 1650000 grids, with the maximum being 0.03 and the minimum being 0.01. The small difference between the voltage pressure test calculation results and the reference values proves that the partial element equivalent circuit method of the volume integral equation algorithm and the moment algorithm has good computational accuracy and precision in large-scale grid computing. The above results indicate that the method proposed by the research institute has good accuracy and multi-layer interconnectivity in extracting circuit parameters, providing theoretical support for the subsequent development of circuit parameter extraction.